A new V-shaped triphenylamine/diketopyrrolopyrrole containing donor material for small molecule organic solar cells1. Issue 83 (9th September 2015) - Wang, Shifan; Yang, Jie; Zhang, Zhiguo; Hu, Yuanyuan; Cao, Xudong; Li, Hai; Tao, Youtian; Li, Yongfang; Huang, Wei
<x xml:space="preserve">Abstract</x> A new V-shaped triphenylamine/diketopyrrolopyrrole based donor material was designed and synthesized, which exhibited a PCE of 3.81% in OSCs.